Supplying and reselling digital content : digital exhaustion in EU copyright and neighbouring rights law - Geiregat, Simon (Edward Elgar Publishing, 2022)
"This book offers a comprehensive and critical evaluation of the digital distribution and ownership of digital content within the EU. The analysis builds on the debate surrounding 'digital exhaustion' and is focused around three generations of supply of digital content: hardcopy sales, downloads and online access. For each generation, the supplying act and the ability to further transfer what was supplied is scrutinized in the light of EU copyright and neighbouring rights law. Going beyond a description of case law, this book highlights inconsistencies and frictions caused by the CJEU and addresses the fate for novel business models, hybrid works and neighbouring rights. Finding that copyright is only one part of the puzzle, Simon Geiregat offers broader perspectives to the transferability discussion by involving impeding digital architecture (technical protection measures), the 'data ownership' debate and by bringing consumer contract law, property law as well as equal treatment into the analysis. Providing a rigorous overview of the law surrounding digital content, this will be a valuable read for academics and practitioners with an interest in EU copyright and the debates on propertization and transferability in the digital context. It will also be beneficial to music and film organizations and distributors involved in supplying digital content in the European market"--